Sa12b Improves Biological Activity of Human Degenerative Nucleus Pulposus Mesenchymal Stem Cells in a Severe Acid Environment by Inhibiting Acid-Sensitive Ion Channels - Wang, Ziyu; Han, Letian; Chen, Haoyu; Zhang, Shengquan; Zhang, Sumei; Zhang, Hua; Li, Yuhao; Tao, Hui; Li, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Sa12b is a wasp peptide that can inhibit acid-sensitive ion channels (ASICs). The biological effects of nucleus pulposus mesenchymal stem cells (NP-MSCs) have not been investigated. Therefore, this study investigated the effect of Sa12b on the biological activity of NP-MSCs through ASICs in the acidic environment of intervertebral disc degeneration (IVDD). In this study, NP-MSCs were isolated from nucleus pulposus (NP) in patients who underwent lumbar disc herniation surgery, identified by flow cytometry and tertiary differentiation, and cultured in vitro in an acidic environment model of IVDD with a pH of 6.2. Proliferation, and apoptosis were observed after different Sa12b concentrations were added to NP-MSCs. The [Ca2+]i was detected using flow cytometry and laser confocal scanning microscopy, and qPCR was used to detect the relative expression of stem cell–associated genes (Oct4, Nanog, Jag1, and Notch1), the relative expression of extracellular matrix–associated genes (collagen II, aggrecan, and SOX-9), and the relative expression of genes encoding ASICs (ASIC1, ASIC2, ASIC3, and ASIC4). WB was used to detect the protein expression of collagen II and aggrecan. Cells isolated and cultured from NP were spindle-shaped and adherent, and they exhibited expansion in vitro, with high expression of CD73 (98.1%), CD90 (97.5%), and CD105 (98.3%) and low expression of HLA-DR (0.93%), CD34 (2.63%), and CD45 (0.33%). With an increase in Sa12b concentration, the proliferation rate of NP-MSCs increased, and the apoptosis rate decreased significantly, reaching the optimal level when the concentration of Sa12b was 8 μg/μL. When the Sa12b concentration was 8 μg/μL and contained the ASIC non-specific inhibitor amiloride, the [Ca2+]i was the lowest, followed by that when the Sa12b concentration was 8 μg/μL. The [Ca2+]i was the highest in the control group. qPCR results showed that as the concentration of Sa12b increased, the relative expression of Oct4, Nanog, Jag1, Notch1, collagen II, aggrecan, and SOX-9 increased, while that of ASIC1, ASIC2, ASIC3, and ASIC4 decreased. In conclusion, Sa12b can improve the biological activity of NP-MSCs in severely acidic environments of IVDD by reducing [Ca2+]i via AISC inhibition. This study provides a new approach for the biological treatment of IVDD.